Effect of Lentivirus-mediated uPA Silencing on the Proliferation and Apoptosis of Chondrocytes and the Expression of MMPs - 史晨辉 王维山 张振东 李长俊 郭风劲 李锋 陈安民 (Journal of Huazhong University of Science and Technology. Medical sciences, 2015)
The lentivirus-mediated u PA interference in the proliferation, apoptosis, and secretion of osteoarthritic chondrocytes was examined in this study. Cells were obtained from the cartilage tissues of New Zealand white rabbits. They were cultured with interleukin（IL）-1β（10 ng/m L） for 24 h and then divided into three groups： u PA-si RNA group（cells transfected with u PA-si RNA lentiviruses）, blank control group（untreated cells）, and negative control group（cells transfected with empty vectors）. Western blotting and real-time quantitative reverse transcription-PCR（RT-QPCR） were performed to detect the protein and m RNA expression levels of u PA, MMP-1, MMP-3, MMP-9, MMP-10, MMP-13 and MMP-14 in osteoarthritic chondrocytes. Cell Counting Kit-8, flow cytometry, and colony formation assay were used to examine the proliferation and apoptosis of chondrocytes. The results showed that after u PA-si RNA transfection, the protein and mR NA expression levels of uP A, MMP-1, MMP-3, MMP-9, MMP-10, MMP-13, and MMP-14 were significantly decreased（P〈0.05 for MMP-1, MMP-9, MMP-10 and MMP-14, P〈0.01 for u PA, MMP-3 and MMP-13）. Cell proliferation and colony formation rate were significantly higher and the cell apoptosis rate was significantly lower in u PA-si RNA group than in control groups（P〈0.01）. The proportion of cells in G0/G1 phase was markedly increased and that in the S phase decreased, and the cell cycle was arrested at the G1/S phase in the control group. In the u PAsi RNA group, the proportion of cells in the S phase was significantly increased, resulting in a different proportion of cells in cell cycle phase（P〈0.01）. It was suggested that the down-regulation of uP A gene could inhibit the expression of MMPs protein and cell apoptosis, increase the proliferation and colony formation of osteoarthritic chondrocytes.